1988
DOI: 10.1016/s0735-1097(98)90063-8
|View full text |Cite
|
Sign up to set email alerts
|

“Nodoventricular” accessory pathway: Evidence for a distinct accessory atrioventricular pathway with atrioventricular node-like properties

Abstract: Two patients are described with recurrent pre-excited tachycardia and electrophysiologic characteristics typically ascribed to a nodoventricular accessory connection. The accessory pathway in each case demonstrated rate-dependent prolongation of conduction time and a low right ventricular insertion site; it was associated with a left bundle branch block configuration during pre-excitation. Intraoperatively, the pathway was demonstrated to originate at the anterior right atrioventricular (AV) anulus and not at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(82 citation statements)
references
References 14 publications
1
80
0
1
Order By: Relevance
“…[2][3][4][5][12][13][14][15][16][17] However, posteroseptal locations could also be found, 7,14 and true nodoventricular fibres have been identified (see Figure 5). 1,14,16 In addition, some of these pathways, so-called 'short'…”
Section: Nodoventricular or Atriofascicular?mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][12][13][14][15][16][17] However, posteroseptal locations could also be found, 7,14 and true nodoventricular fibres have been identified (see Figure 5). 1,14,16 In addition, some of these pathways, so-called 'short'…”
Section: Nodoventricular or Atriofascicular?mentioning
confidence: 99%
“…Accessory pathways with decremental conduction properties that connected the atrium to the right bundle branch (RBB) were subsequently mapped mainly at the lateral aspect of the tricuspid annulus, and thus the term atriofascicular was also adopted. [2][3][4] We know now that decrementally conducting connections can be between the right atrium or the AV node and the right ventricle in or close to the RBB. [5][6][7] Thus, although they are anatomically distinct from the initially described nodoventricular pathway, they present with similar electrocardiographic and electrophysiological characteristics and the term 'Mahaim' has been adopted to describe pathways with the following features:…”
mentioning
confidence: 99%
“…1 -Continuous programmed stimulation in high right atrium showing: (1A) with a stimulation cycle (S1-S1) of 460 ms, mild ventricular preexcitation occurs (*); (1B) continuing the tracing, progressive ventricular preexcitation is observed during the stimulation at progressively shorter cycles (S1-S1=390 ms) (**) with extension of the A-H and A-V intervals. pharmacological treatment, catheter ablation 5,6,[9][10][11][12]18 , and surgery 7,12 . The first experiences with catheter ablation used high-energy shocks in the atrioventricular node region.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies [2][3][4][5][6] showed that these fibers had special properties, such as exclusive anterograde and decremental conduction, and could be located in sites distant from the atrioventricular node and eliminated by surgery or catheter ablation. Recently, most of these pathways have been classified as atriofascicular fibers that connect the right atrium to distal portions of the right branch of the His bundle with decremental properties 7,8 . Because they have different anatomical and electrophysiological characteristics, the following special ablation techniques have been considered: 1) atrial stimulation (pace-mapping) along the tricuspid ring, looking for the shortest "spike-Delta" interval 9 ; 2) mapping with extrastimuli during antidromic tachycardia, searching for the point of greatest "preexcitation" of the subsequent QRS; and 3) mapping of the activation potential of the fiber in sinus rhythm [10][11][12][13] .…”
mentioning
confidence: 99%
“…1213 Furthermore, there is a growing suspicion that nodoventricular bypass tracts do not, in actuality, originate from the node but are more likely to be atrioventricular or atriofascicular accessory pathways with nodelike decremental properties. [13][14][15] A wide QRS tachycardia with atrioventricular dissociation in such instances would be impossible. Therefore, a tachycardia that may be explained by this improbable and purely hypothetical mechanism is more likely Macro-HPS VT.…”
Section: Efficacy Of Right Bundle Ablationmentioning
confidence: 99%